2018
DOI: 10.3390/medsci6030054
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: Activation and Inhibition in Health and Disease

Abstract: There are many types of cell death, each involving multiple and complex molecular events. Cell death can occur accidentally when exposed to extreme physical, chemical, or mechanical conditions, or it can also be regulated, which involves a genetically coded complex machinery to carry out the process. Apoptosis is an example of the latter. Apoptotic cell death can be triggered through different intracellular signalling pathways that lead to morphological changes and eventually cell death. This is a normal and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 159 publications
(206 reference statements)
0
38
0
Order By: Relevance
“…The caspase-cascade system is entangled in the induction, transduction, and amplification of intracellular apoptotic signals. Caspase-3 is one of the executer caspases involved in apoptosis [64]. Caspase-3 immunostained sections obtained from the untreated diabetic group showed a significant increase in the cytoplasmic immunoreactivity when compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…The caspase-cascade system is entangled in the induction, transduction, and amplification of intracellular apoptotic signals. Caspase-3 is one of the executer caspases involved in apoptosis [64]. Caspase-3 immunostained sections obtained from the untreated diabetic group showed a significant increase in the cytoplasmic immunoreactivity when compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…It seems that these pathways are irrelevant; however, they can actually be linked through Bcl-2 family proteins. Research on the mechanisms of apoptosis in cells has shed light on the fact that the Bcl-2 family plays a central role in the apoptotic pathway ( 22 ) ( Fig. 1 ).…”
Section: Central Role Of the Bcl-2 Family In The Apoptotic Pathwaymentioning
confidence: 99%
“…Apoptosis as a process of regulating cell death, is mainly composed of complex intracellular signal networks. There are three different triggering pathways, including the exogenous (classical death receptor), endogenous (subdivided into mitochondria-and ER stress-induced types) and non-caspase-dependent pathways [27][28][29][30]. The Fas/FasL pathway is the most classical death receptor pathway and plays an important role in apoptosis [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Common ER stress inducers include TM [37][38][39]. Since caspase12 is involved in the ER stress pathway and is one of its molecular markers [17,30], we examined the marker protein cleaved-caspase 12 of the ER stress pathway. Our results showed that there was no change in the expression of cleaved-caspase 12 after AngII-induced injury.…”
Section: Discussionmentioning
confidence: 99%